The Dynamics of Sufism Based on Plural Indonesian Society: A Study of the Socio-Academic Role of KH. Nur Salim in Malang, East Java - Syaifuddin, Syaifuddin; Suwatah, Suwatah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
In the late twentieth century, he witnessed a significant shift in Islamic discourse in Indonesia, particularly with the rise of egalitarianism and the indigenization of Islam. Against this backdrop, this study investigates KH. Nur Salim's pivotal role in adapting Sufism to a pluralistic society in Malang, East Java. It aims to explore how his down-to-earth approach effectively integrated spiritual values with social life, fostering a form of Sufism that suits the needs of modern society. Using qualitative phenomenological methods, the research captured the lived experiences and perceptions of the community regarding KH Nur Salim in his socio-academic role. Data was collected through in-depth interviews, participant observation, and document analysis to understand the phenomenon comprehensively. The findings show that KH. Nur Salim, centered on four pillars- patience, humility, acceptance, and generosity- not only advances individual spirituality but also strengthens social cohesion in a diverse society. This approach is in line with theories that emphasize contextual adaptation of religious teachings, contributing to the discourse on the role of religion in promoting pluralism and tolerance. However, the study acknowledges limitations related to geographical coverage and methodological challenges, which may impact the generalizability of the findings. These insights have implications for the broader application of Sufism in pluralistic contexts globally.